PENERAPAN PENGENDALIAN INTERNAL SISTEM INFORMASI AKUNTANSI PERSEDIAAN PT. KASOEM VISION CARE - Ahmad Rizal Fitrananda, (2022)
This qualitative study aims to determine how the implementation of internal control of the inventory accounting information system at PT Kasoem Vision Care. The implementation of control is measured based on the elements of the COSO, while the accounting information system is measured based on the components of the accounting information system based on the elements proposed by Romney & Steinbart. This study uses an interpretive paradigm with an ethnomethodological approach. Data collection techniques in this study used direct observation at the research site, conducted interviews with key informants and supporting informants, and carried out documentation. Overall, this research shows that PT Kasoem Vision Care has implemented the internal control accounting information system in accordance with the elements of COSO control and accounting information system components proposed by Romney & Steinbart. However, there are still shortcomings, such as the implementation of HR policies experiencing, inconsistent attitudes from employees, obstacles related to authorization still occur, and monitoring of merchandise assets is still a problem.